2013
DOI: 10.1055/s-0032-1333416
|View full text |Cite
|
Sign up to set email alerts
|

A Variation of the Cords of the Brachial Plexus on the Right and a Communication between the Musculocutaneous and Median Nerves on the Left Upper Limb: A Unique Case

Abstract: During routine anatomical dissection of the upper extremity of a 64-year-old cadaver for educational purposes, we observed variations in the brachial plexus on each side. On the right an anomaly of cord formation was present and on the left there was a communication between the musculocutaneous nerve (MCN) and median nerve (MN). On the right side the brachial plexus showed two trunks, superior (C5 and C6) and inferior (C7, C8, and T1); the middle trunk was absent. The superior trunk bifurcated into anterior an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 14 publications
(30 reference statements)
1
3
0
4
Order By: Relevance
“…The MCN in the present case did not pierce the coracobrachialis muscle and there was an additional communicating branch from the MN to MCN. Taken together, the present communications between the MCN and MN observed in the left arm of this cadaver did not resemble any variations described previously [3,8,14,16,17,20,28,33]. In this case, injury of the MCN in the upper arm superior to the proximal communication may cause paralysis of the elbow flexor and unexpected paralysis of flexor and/or thenar muscles.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…The MCN in the present case did not pierce the coracobrachialis muscle and there was an additional communicating branch from the MN to MCN. Taken together, the present communications between the MCN and MN observed in the left arm of this cadaver did not resemble any variations described previously [3,8,14,16,17,20,28,33]. In this case, injury of the MCN in the upper arm superior to the proximal communication may cause paralysis of the elbow flexor and unexpected paralysis of flexor and/or thenar muscles.…”
Section: Discussionsupporting
confidence: 73%
“…Kaus and Wotowicz [14] reported two junctions of the MN and MCN similar to the present case but without an additional communicating branch from the MN to the MCN. Kirazli et al [16] reported a case of MCN piercing the coracobrachialis muscle and terminating by giving a communicating branch to the MN. From this branch, the branches to the brachialis muscle and LACN were given.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Variations in the formation of the BP's trunks [4,7,[23][24][25], as well as in their relation to the scalene muscles [5,18], have been described in the literature. Certain variations are linked to the neurogenic thoracic outlet syndrome (TOS) [9], due to the proximity of the muscle fibres and the nerves.…”
Section: Introductionmentioning
confidence: 99%
“…No lado direito, havia um ramo comunicante do MCN para o MN no terço inferior da região do braço. Este ramo comunicante também deu origem a um ramo muscular para o músculo braquial e o nervo cutâneo lateral do antebraço(Kirazli et al, 2013).Tais achados, influenciam diretamente na conduta de procedimentos cirúrgicos nas áreas de membros superiores, uma vez que toda a estrutura típica do plexo braquial foi alterada devido à ausência do tronco médio. Nesse contexto, maiores conhecimentos sobre tais variações são imprescindíveis tendo em vista que o seu desconhecimento pode ser um preditor de para piora de desfechos clínicos.CONCLUSÃOObservou-se que as variações anatômicas do plexo braquial não são achados incomuns.…”
unclassified